Democracy, agency, and the state theory with comparative intent - O'Donnell, Guillermo A. (Oxford : Oxford University Press, 2010)
One of the pioneers of democratization studies presents the culmination of a lifetime's study in the form of a far-reaching and profound analysis of the relationship between the state and democracy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Democracy; State, The